The validity of Arabic version of Vestibular Disorder Activities of Daily Living Scale in common episodic vestibular disorders during and in between the attacks: a cross-sectional study - Halla Badawood; Manar Aldosari; Sara Alshugihi; Alfarghal Mohamad; Hadi Al-Hakami; Mohammed Al-Garni (The Egyptian Journal of Otolaryngology, 2022)
Abstract Background Activities of daily living (ADLs) are activities oriented toward taking care of one’s own body independently. Vestibular Disorder Activities of Daily Living Scale (VADL) includes 28 questions designed to specifically assess the effects of different vestibular disorders on activities of daily living and assess the validity and reliability of the Arabic version of VADL and applying it to assess severity of the attacks related to most common episodic vestibular disorders. The Arabic version of VADL was distributed to 52 participants, recruiting two participants per question. The participants filled up the Arabic version of VADL scale, in-between and during the vertigo episodes. Results All participants have been diagnosed as having one of these vestibular disorders benign paroxysmal positional vertigo (BPPV), vestibular migraine, and Meniere’s disease. The reliability analysis was calculated with Cronbach’s alpha score, and it was 0.980, indicating high reliability. There was a positive correlation between the VADL scores during and in between the attacks of vertigo for the three diseases (p = 0.03). There was a statistical difference between the three disorders during and in between the attacks (p-value during the attack < 0.0001, p-value in between the attacks = 0.046). Meniere’s disease had the most negative impacts on daily activities performance, followed by BPPV, and vestibular migraine had the least effect. There was statistically significant correlation between VADL and visual analog scale (VAS) during and in between the attacks (Pearson correlation 0.74, p < 0.0001). Conclusion The Arabic version of VADL scale has high validity and an excellent reliability among our demographic population. Meniere’s disease has the worst impact on patients’ performance in activities of daily living compared to BPPV and vestibular migraine.